PCDD and PCDF emissions from simulated sugarcane field burning - Gullett, Brian K; Touati, Abderrahmane; Huwe, Janice; Hakk, Heldur (Environmental science & technology, 2006)
The emissions from simulated sugarcane (Saccharum officinarum) field burns were sampled and analyzed for polychlorinated dibenzodioxins and dibenzofurans (PCDDs and PCDFs). Sugarcane leaves from Hawaii and Florida were burned in a manner simulating the natural physical dimensions and biomass density found during the practice of preharvest field burning. Eight composite burn tests consisting of 3-33 kg of biomass were conducted, some with replicate samplers. Emission factor calculations using sampled concentration and measured mass loss compared well to rigorous carbon balance methods commonly used in field sampling. The two sources of sugarcane had distinctive emission levels, as did tests on separate seasonal gatherings of the Florida sugarcane. The average emission factor for two tests of Hawaii sugarcane was 253 ng toxic equivalents (TEQ)/kg of carbon burned (ng TEQ/kg(Cb)) (rsd = 16%) and for two gatherings of Florida sugarcane was 25 ng TEQ/kg(Cb) (N = 4, rsd = 50%) and 5 ng TEQ/kg(Cb) (N = 2, rsd = 91%). The Hawaii sugarcane, as well as most of the Florida sugarcane, had emission values which were well above the value of 5 ng TEQ/kg(Cb) commonly attributed to biomass combustion. Application of this emission factor range to the amount of U.S. sugarcane fields burned suggests that this practice may be a relatively minor source of PCDDs and PCDFs in the U.S. national inventory, but the limited sample size and range of results make this conclusion tenuous.